Facilitation of the main generator source of earthworm muscle contraction by a peripheral neuron - Y.C. Chang; Z. Assmé; A.B. Bartoszeck (Brazilian Journal of Medical and Biological Research, 1998)
A constant facilitation of responses evoked in the earthworm muscle contraction generator neurons by responses evoked in the neurons of its peripheral nervous system was demonstrated. It is based on the proposal that these two responses are bifurcations of an afferent response evoked by the same peripheral mechanical stimulus but converging again on this central neuron. A single-peaked generator response without facilitation was demonstrated by sectioning the afferent route of the peripheral facilitatory modulatory response, or conditioning response (CR). The multipeaked response could be restored by restimulating the sectioned modulatory neuron with an intracellular substitutive conditioning stimulus (SCS). These multi-peaked responses were proposed to be the result of reverberating the original single peaked unconditioned response (UR) through a parallel (P) neuronal circuit which receives the facilitation of the peripheral modulatory neuron. This peripheral modulatory neuron was named "Peri-Kästchen" (PK) neuron because it has about 20 peripheral processes distributed on the surface of a Kästchen of longitudinal muscle cells on the body wall of this preparation as revealed by the Lucifer Yellow-CH-filling method.